2019
DOI: 10.1021/acsami.9b17714
|View full text |Cite
|
Sign up to set email alerts
|

The Dissociation Rate of Acetylacetonate Ligands Governs the Size of Ferrimagnetic Zinc Ferrite Nanocubes

Abstract: Magnetic nanoparticles are critical to a broad range of applications, from medical diagnostics and therapeutics to biotechnological processes and single molecule manipulation. To advance these applications, facile and robust routes to synthesize highly magnetic nanoparticles over a wide size range are needed. Here, we demonstrate that changing the degassing temperature of thermal decomposition of metal acetylacetonate precursors from 90 to 25°C tunes the size of ferrimagnetic Zn x Fe 3-x O 4 nanocubes from 25 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…Increasing the ratio of acetylacetone to oleic acid ligands results in assembly of small magnetic zinc ferrite subdomains into 100 nm cubic‐shape particles, due to less bulkiness and higher mobility of acetylacetone ligands as compared to oleic acid. [ 152 ]…”
Section: Defect‐engineering In Iron Oxide Nanoparticlesmentioning
confidence: 99%
“…Increasing the ratio of acetylacetone to oleic acid ligands results in assembly of small magnetic zinc ferrite subdomains into 100 nm cubic‐shape particles, due to less bulkiness and higher mobility of acetylacetone ligands as compared to oleic acid. [ 152 ]…”
Section: Defect‐engineering In Iron Oxide Nanoparticlesmentioning
confidence: 99%
“…The particle design is based on our previous expertise and results, where we have demonstrated the impact of synthesis conditions on size and shape of the particles. 22 Other studies have shown that the choice of surfactant types also plays a crucial role in the size, shape, and growth of the particles. 13,16,23,24 Here, we have optimized four crucial synthesis parameters: feed ratio of dopants, choice of solvents to stabilize growth temperature, choice of surfactants to control the shape, and heating ramp rate to favour nucleation and growth of the particles (for details see SI).…”
Section: Resultsmentioning
confidence: 99%
“…As Zn doping increases the particle size dramatically, 22 we use 0.25 mol equivalent of Zn for 1.0 mol equivalent of Fe. This produced about 8.1±0.6 nm NCs.…”
Section: Resultsmentioning
confidence: 99%
“…This is likely attributed to the slower decomposition rate of the Zn precursor in comparison to the cobalt precursor, in the reaction mixture. 43 Indeed, when looking at the decomposition temperature measured by thermogravimetric analysis of Zn(acac) 2 , it was found that it is higher (300 °C) than that of Co(acac) 2 (250 °C). 44,45 …”
Section: Resultsmentioning
confidence: 99%
“…This is likely attributed to the slower decomposition rate of the Zn precursor in comparison to the cobalt precursor, in the reaction mixture. 43 Indeed, when looking at the decomposition temperature measured by thermogravimetric analysis of Zn (acac) 2 , it was found that it is higher (300°C) than that of Co (acac) 2 (250°C). 44,45 To reduce the Zn-ferrite NC size, the amount of surfactant (DA) in the synthesis was increased from 6 to 7 mmol (corresponding to a surfactant to metal Fe + Zn molar ratio of 4.7) while keeping the rest of the precursors as in the first synthesis attempt for Zn-ferrite (1 mmol Fe (acac) 2 , 0.5 mmol Zn(acac) 2 , Fig.…”
Section: Synthesis Of Mixed Ferrite Ncs: Control Over the Compositionmentioning
confidence: 99%